2022
DOI: 10.5005/japi-11001-0138
|View full text |Cite
|
Sign up to set email alerts
|

Blood Stream Infection Caused by Carbapenem-resistant Chryseobacterium indologenes Harboring blaNDM-1 Gene Isolated from a Tertiary Care Hospital in Tripura: An Emerging Threat

Abstract: Objectives: Chryseobacterium indologenes has recently been identified as an inherently drug-resistant organism, responsible for a wide spectrum of infections, mainly device-associated infections in hospital settings. The presence of carbapenem resistance due to blaNDM-1 metallo-β-lactamase (MBL) gene further complicates the matter, leading to widespread dissemination of carbapenem resistance. This study aims to find out the presence of blaNDM-1 gene among C. indologenes strains causing bloodstream infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…9,10 C. indologenes is a species intrinsically resistant to aminoglycosides, first-generation cephalosporins, aminopenicillins and aztreonam, which limits therapeutic options. 11 The emergence of carbapenemresistant strains of C. indologenes has further restricted antibiotic therapy, with strains producing metallo-β-lactamases (MBL) enzymes representing the greatest threat. 12 MBL-producing bacteria are resistant to all penicillins, cephalosporins and carbapenems, in addition to being unaffected by available β-lactamase inhibitor antibiotics, including the most advanced ones, such as Avibactam or Vaborbactam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 C. indologenes is a species intrinsically resistant to aminoglycosides, first-generation cephalosporins, aminopenicillins and aztreonam, which limits therapeutic options. 11 The emergence of carbapenemresistant strains of C. indologenes has further restricted antibiotic therapy, with strains producing metallo-β-lactamases (MBL) enzymes representing the greatest threat. 12 MBL-producing bacteria are resistant to all penicillins, cephalosporins and carbapenems, in addition to being unaffected by available β-lactamase inhibitor antibiotics, including the most advanced ones, such as Avibactam or Vaborbactam.…”
Section: Discussionmentioning
confidence: 99%
“…14 The isolation of C. indologenes strains harboring the blaNDM-1 gene is of great concern as it may lead to widespread resistance to carbapenems through horizontal gene transfer. 11 Reports from the SENTRY Antimicrobial Surveillance program demonstrated that the group of drugs that have the greatest activity against C. indologenes are the quinolones (85-100%). Among β-lactams, piperacillin-tazobactam showed the highest sensitivity (90%), while carbapenems had a poor sensitivity profile (10-15%).10 In more recent studies in India, the highest sensitivity was for the quinolone group (100%), which agreed with the SENTRY Surveillance findings.…”
Section: Discussionmentioning
confidence: 99%